Telecommunications Role in Economic Growth with Respect to Pakistan (Global Journal of Management and Business Research, 2012)
This study investigates the relationship between economic growth and development in the telecom sector through foreign direct Investment (FDI) and making good infrastructure for land line and cell phones. We check the impact of the telecom sector, independent variable, on the economic growth, dependent variable, through using questionnaire based of five options likert scale then we used the simple regression model as statistical instrument to check the impact. In this study we shows that the growth in the telecom sector is not consider as a whole growth in the economy.
Keywords: Telecom; Economic growth; developing countries